Pinning Down Viral Proteins: A New Prototype for Virus–Host Cell Interaction - Kojima, Yoshitsugu; Ryo, Akihide (Frontiers in Microbiology, 2010)
Pin1 is an enzyme that specifically catalyzes the cis-trans isomerization of phosphorylated serine/threonine-proline (pSer/Thr-Pro) motif in its substrate proteins. Recent studies demonstrate that stability of several viral proteins is regulated by phosphorylation-dependent prolyl-isomerization by a host factor Pin1. Pin1 is now positioned as an important modulator of the molecular crosstalk between virus and host cells and could be a unique target for anti-virus therapy. This new type of post-translational modification by Pin1 might be involved in the regulation of other viral proteins.